2011
DOI: 10.1371/journal.pone.0025060
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cytokine Levels and NK Cell Activation Associated with Influenza

Abstract: Several studies have highlighted the important role played by murine natural killer (NK) cells in the control of influenza infection. However, human NK cell responses in acute influenza infection, including infection with the 2009 pandemic H1N1 influenza virus, are poorly documented. Here, we examined changes in NK cell phenotype and function and plasma cytokine levels associated with influenza infection and vaccination. We show that absolute numbers of peripheral blood NK cells, and particularly those of CD56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 59 publications
5
50
2
Order By: Relevance
“…Also the intracellular cytokine staining of IFN-γ, TNF, IL-10, IL-13 and IL-17A in CD3 -56 bright and CD3 -56 dim cells respectively, showed no significant differences between patients and controls. Although previous reports showed that expression of activation markers on NK cells are increased in some inflammatory conditions (Evans et al, 2011, Jost et al, 2011 we could not confirm these findings in our study populations; probably the systemic inflammation is too low in CAD or reduced by treatment, to induce these activation markers on NK cells. In contrast, our previous studies showed that NK cells in CAD were more prone to become activated and undergo apoptosis (Jonasson et al, 2005, Li et al, 2008 and also in paper II we found that proportions of NK type 1 cells (IL-18R + ) were increased in ACS compared to SA patients.…”
Section: Nk Subpopulations (Paper Iii)contrasting
confidence: 92%
See 2 more Smart Citations
“…Also the intracellular cytokine staining of IFN-γ, TNF, IL-10, IL-13 and IL-17A in CD3 -56 bright and CD3 -56 dim cells respectively, showed no significant differences between patients and controls. Although previous reports showed that expression of activation markers on NK cells are increased in some inflammatory conditions (Evans et al, 2011, Jost et al, 2011 we could not confirm these findings in our study populations; probably the systemic inflammation is too low in CAD or reduced by treatment, to induce these activation markers on NK cells. In contrast, our previous studies showed that NK cells in CAD were more prone to become activated and undergo apoptosis (Jonasson et al, 2005, Li et al, 2008 and also in paper II we found that proportions of NK type 1 cells (IL-18R + ) were increased in ACS compared to SA patients.…”
Section: Nk Subpopulations (Paper Iii)contrasting
confidence: 92%
“…+ cells are few but may be increased in acute inflammatory diseases (Evans et al, 2011, Jost et al, 2011. On the other hand CD69 is frequently more expressed on T cells in LN, suggested to promote lymphocyte retention (Shiow et al, 2006).…”
Section: Identification Of Lymphocyte Subpopulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…During asymmetric division, parental T cells yield both effector (CD4 − CD8 hi ) and long lived memory (CD4 − CD8 lo ) cytotoxic cells [3032]. Due to the restricted number of markers labeled in this study, the CD4 − CD8 lo cytotoxic T memory cells could not be distinguished from the NK cells, which bear the CD4 − CD8 lo phenotype and upregulate CD25 as well [33]. …”
Section: Resultsmentioning
confidence: 99%
“…IL-2R signalling activates IKKα which results in the recruitment of IκBα and this stimulates the binding of NFκB components resulting in an enhanced PRF1 expression in NK cells [22]. Relatively low levels of IL-2 are present in the plasma during influenza infection causing a possible reduction in NK related IFN-γ secretion and cytotoxic activity [24]. Reduced cytotoxic activity is a hallmark of CFS/ME and this may promote viral thrive, persistence and suppressed pathogen clearance.…”
Section: Discussionmentioning
confidence: 99%